2022
DOI: 10.1139/er-2021-0042
|View full text |Cite
|
Sign up to set email alerts
|

Natural disturbance regimes for implementation of ecological forestry: a review and case study from Nova Scotia, Canada

Abstract: Ecological forestry is based on the idea that forest patterns and processes are more likely to persist if harvest strategies produce stand structures, return intervals, and severities similar to those from natural disturbances. Taylor et al. (2020) reviewed forest natural disturbance regimes in Nova Scotia, Canada, to support implementation of ecological forestry. In this follow-up paper, we 1) review use of natural disturbance regimes to determine target harvest rotations, age structures, and residual stand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…We also explored the timing of leaf phenology itself as an ecological integrity indicator, though found that variation due to other factors was of a similar magnitude or in some cases greater than variation due to disturbance or stress, and that this approach neglects the role of developed frost hardiness, which may not vary consistently with phenology between species (see Zohner et al, 2020). Extreme weather like Hurricane Dorian (>10,000 ha of forest damage), which led to widespread forest damage on the order of >500 ha, may affect Nova Scotia, the province in which 22 of the 33 Acadian Phenocam Network cameras are managed, as frequently as once every seven years (MacLean et al, 2022; Taylor et al, 2020). Insect outbreaks such as that of Choristoneura fumiferana , the spruce budworm, which lead to widespread damage of predominant native tree species, may also occur in Nova Scotia once every 30–40 years (Smith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also explored the timing of leaf phenology itself as an ecological integrity indicator, though found that variation due to other factors was of a similar magnitude or in some cases greater than variation due to disturbance or stress, and that this approach neglects the role of developed frost hardiness, which may not vary consistently with phenology between species (see Zohner et al, 2020). Extreme weather like Hurricane Dorian (>10,000 ha of forest damage), which led to widespread forest damage on the order of >500 ha, may affect Nova Scotia, the province in which 22 of the 33 Acadian Phenocam Network cameras are managed, as frequently as once every seven years (MacLean et al, 2022; Taylor et al, 2020). Insect outbreaks such as that of Choristoneura fumiferana , the spruce budworm, which lead to widespread damage of predominant native tree species, may also occur in Nova Scotia once every 30–40 years (Smith et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding which species are robust, resilient, or susceptible to global change through the monitoring protocol we proposed here will provide insight for effective conservation and management activities (Chamberlain et al, 2019). This would allow for informed decisions regarding ecological forestry practices in the context of global change, which species to plant for remediation following disturbance events, and which species may require additional focus for protection from disturbance agents (MacLean et al, 2022; Price et al, 2013; Taylor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific knowledge is used to guide tangible outcomes in forest management such as designing silvicultural prescriptions (which determine the approach to harvesting and regeneration of trees; e.g. Achim et al, 2022; MacLean et al, 2021) and conserving forest biodiversity (e.g. Scullion et al, 2019), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Understandings and predictions of future leaf phenology patterns in the eastern Acadian Forest Region are limited due to a lack of observational data, compounded by a highly variable climatic regime (Garbary & Hill, 2021 ; MacLean et al, 2022 ; Pearson & D'Orangeville, 2022 ; Steenberg et al, 2013 ; Taylor et al, 2020 ). A study comparing climate normals across Nova Scotia from 1961 to 1990 and 1991 to 2020 found that warming in the autumn has been more pronounced relative to spring, with a larger relative increase in the number of frost‐free days in autumn (Garbary & Hill, 2021 ).…”
Section: Introductionmentioning
confidence: 99%